THE EFFECTIVENESS OF OFFICE MANAGEMENT SYSTEMS IN POSO KOTA DISTRICT - Nuraisyah, Nuraisyah; Haryono, Dandan; M, Mustainah; Nofitri, Nofitri; Mertina, Serly; Kristian, Kristian; Rivai, Abdul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to explore and analyze the effectiveness of office management systems in Poso Kota District, focusing on goal achievement, departmental integration, and adaptation to change. Using a qualitative descriptive approach, the study describes, analyzes, and interprets current conditions in Poso District, Poso Regency. The research was conducted over one fiscal year using primary data from in-depth interviews and systematic observations, as well as secondary data from literature and official documents. Informants were selected purposively based on their understanding of the phenomenon under study. The research instruments included interview guidelines and the researcher as the main instrument. Data analysis followed an interactive model, encompassing data collection, condensation, presentation, verification, and conclusion drawing. Findings indicate that despite structured steps to manage policy and technological changes, the office management system faces significant challenges in achieving administrative efficiency, optimal public service, effective integration between departments, and adaptation to a dynamic work environment. In terms of the three main dimensions—goal achievement, integration, and adaptation—the office management system in Poso Kota District still requires improvements in internal communication, enhanced use of information technology, and staff training to optimize operations and organizational responsiveness.